WORM INFECTIONS ON STRAY CATS AT THE GUNUNG GEDE CAMPUS OF IPB - Siagian, Tetty Barunawati (IPB University, 2024)
IPB Gunung Gede is one of the campuses owned by IPB University. Stray cats are found in this campus area with quite a large population. One of the diseases found in wild cats is a disease caused by worm infection (helminthiasis). This study used feces samples from 18 stray cats. The stool examination carried out is macroscopic and microscopic examination. The results of the macroscopic examination found feces with a soft consistency, with a yellow, greenish yellow to brownish yellow color, the feces did not have a foul smell, but was typical of cat feces, there was no fragmentation of worms, mucus and blood. The results of microscopic examination using native and flotation methods found the presence of Ascarid and Strongylid worm eggs. The types of adult worms that have these eggs are Toxocara cati and Ancylostoma spp. The presentation of worm infections in stray cats on the IPB Gunung Gede Campus is 85%. The cause is thought to be due to a large population which makes it easy for worm eggs to spread to stray cats.